2015
DOI: 10.5817/sp2015-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Surrogate Grandparents as Actors in Intergenerational Learning

Abstract: Current social changes that also affect the situation in the Czech

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…These findings also make us rethink the relationship between family and learning. The family is not only a hub where we live, but also an important site for lifelong learning, a micro-learning unit on which the construction of a learning society depends, 20 as Rabušicová et al (2015), Hoff (2007) and Cherri Ho (2010) have explained. Our findings suggest that intergenerational learning could be a powerful impetus for building a learning society (Cabanillas 2011).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings also make us rethink the relationship between family and learning. The family is not only a hub where we live, but also an important site for lifelong learning, a micro-learning unit on which the construction of a learning society depends, 20 as Rabušicová et al (2015), Hoff (2007) and Cherri Ho (2010) have explained. Our findings suggest that intergenerational learning could be a powerful impetus for building a learning society (Cabanillas 2011).…”
Section: Discussion and Limitationsmentioning
confidence: 99%
“…A number of studies have found that families, schools, communities and the government – among others – can play leading roles in developing intergenerational learning. Milada Rabušicová et al ( 2015 ) found that families play a fundamental role in carrying out intergenerational learning. Andreas Hoff ( 2007 ) claims that intergenerational learning involves informal communication among family members to convey knowledge, skills, social norms and values.…”
Section: Intergenerational Learningmentioning
confidence: 99%